Experimental study on the collapse-resistant performance of unbonded prestressed PC beam-column sub-assemblages with pinned connections - Xu, Wenliu; Wang, Licheng (Engineering structures, 2023)
•A method of using pinned connection and unbonded posttensioning strands (UPSs) to mutually improve the collapse-resistant performance of precast concrete structures was proposed in this study.•The pinned connections are used for connecting precast beams with columns at the precast beam ends, and UPSs with straight profile are placed at the bottom of beam cross-section.•In order to investigate whether the proposed method can enhance collapse-resistant capacity of precast concrete structures, static progressive collapse tests were conducted for the newly proposed precast concrete frame substructures with UPSs (UPPC frame substructures) and without UPSs (PC frame substructure).•Influences of effective prestress level upon the collapse-resistant capacity of UPPC substructure were investigated.•Three-dimensional finite element models (FEMs) was developed to simulate the progressive collapse behavior of the tesed UPPC and PC substructures by using ABAQUS software. In precast concrete frame structures, it is imperative that beam-to-column connection has appropriate robustness and reliable axial resistance to defense against progressive collapse. Hence, a method of using pinned connection and unbonded posttensioning strands (UPSs) to mutually improve the collapse-resistant performance of precast concrete structures was proposed in this study. The pinned connections are used for connecting precast beams with columns at precast beam ends, and UPSs with straight profile are placed at the bottom of beam cross-section. In order to investigate whether the proposed method can enhance collapse-resistant capacity of precast concrete structures, static progressive collapse tests were conducted for the newly proposed precast concrete frame substructures with UPSs (UPPC frame substructures) and without UPSs (PC frame substructure). Moreover, influences of effective prestress level upon the collapse-resistant capacity of UPPC substructure were also investigated. Test results demonstrated that, similar to conventional RC frame structure, the compressive arch action (CAA) and catenary action (CTA) could also develop in the proposed UPPC substructures to avert progressive collapse. The UPPC substructure was able to develop 32% higher CAA capacity and 162% larger CTA capacity as compared to the PC substructure, indicating that the UPSs play a positive role in enhancing both its CAA and CTA. The CTA capacity of the PC substructure was 53.8% higher than that of CAA, which signifies that the pinned connection can be employed to improve structural robustness to mitigate progressive collapse. In addition, the increase of effective prestress level of UPSs is beneficial to the enhancement of CAA capacity of the UPPC substructure. However, higher effective prestress level is limited to improve its CTA capacity due to lower deformation capacity of UPSs. Subsequently, three-dimensional finite element models (FEMs) of the UPPC and PC substructures were developed by using ABAQUS software. By comparing experimental data with FEM results, it was concluded that the FEM could accurately predict the load–displacement curves, crack patterns and reinforcing ruptures of all the test specimens.